Equation:
A = P(1 + rt)
How to do it:
First, converting R percent to r a decimal
r = R/100 = 2.5%/100 = 0.025 per year,
putting time into years for simplicity,
9 months ÷ 12 months/year = 0.75 years,
then, solving our equation
A = 600(1 + (0.025 × 0.75)) = ___
What is it?
Answer:
20 is 1/10 of 200.
Step-by-step explanation:
100*(1/10) = 10
200*(1/10) = 20
Since 100 times 1/10 is 10, all you have to do is double it. So now, 200 times 1/10 is 20.
:) Hope this helps!
The table is missing in the question. The table is provided here :
Group 1 Group 2
34.86 64.14 mean
21.99 20.46 standard deviation
7 7 n
Solution :
a). The IV or independent variable = Group 1
The DV or the dependent variable = Group 2
b).
![$H_0: \mu_1 = \mu_2$](https://tex.z-dn.net/?f=%24H_0%3A%20%5Cmu_1%20%3D%20%5Cmu_2%24)
![$H_a:\mu_1 < \mu_2$](https://tex.z-dn.net/?f=%24H_a%3A%5Cmu_1%20%3C%20%5Cmu_2%24)
Therefore, ![$t = \frac{\bar x_1 - \bar x_2}{\sqrt{\frac{s_1^2}{n_1}+\frac{S_2^2}{n_2}}}$](https://tex.z-dn.net/?f=%24t%20%3D%20%5Cfrac%7B%5Cbar%20x_1%20-%20%5Cbar%20x_2%7D%7B%5Csqrt%7B%5Cfrac%7Bs_1%5E2%7D%7Bn_1%7D%2B%5Cfrac%7BS_2%5E2%7D%7Bn_2%7D%7D%7D%24)
![$t = \frac{34.86 - 64.14}{\sqrt{\frac{21.99^2}{7}+\frac{20.46^2}{7}}}$](https://tex.z-dn.net/?f=%24t%20%3D%20%5Cfrac%7B34.86%20-%2064.14%7D%7B%5Csqrt%7B%5Cfrac%7B21.99%5E2%7D%7B7%7D%2B%5Cfrac%7B20.46%5E2%7D%7B7%7D%7D%7D%24)
t = -2.579143
Now, ![$df = min(n_1 - 1, n_2 - 1)$](https://tex.z-dn.net/?f=%24df%20%3D%20min%28n_1%20-%201%2C%20n_2%20-%201%29%24)
df = 7 - 1
= 6
Therefore the value of p :
![$=T.DIST(-2.579143,6,TRUE)$](https://tex.z-dn.net/?f=%24%3DT.DIST%28-2.579143%2C6%2CTRUE%29%24)
= 0.020908803
The p value is 0.0209
![$p< 0.05$](https://tex.z-dn.net/?f=%24p%3C%200.05%24)
So we reject the null hypothesis and conclude that ![$\mu_1 < \mu_2$](https://tex.z-dn.net/?f=%24%5Cmu_1%20%3C%20%5Cmu_2%24)
Answer:
i feel this is an incomplete picture
Step-by-step explanation:
Answer:
Step-by-step explanation:
nth term = a +(n-1)d
a3 = 116 ; a + 2d = 116 ---------(i)
a7 = 180; a + 6d = 180 -------(ii)
multiply (ii) by -1. so a will be eliminated
a + 2d = 116 ---------(i)
(ii)*-1 <u>-a - 6d = -180</u> -------(ii) { Now add the two equations}
- 4d = -64
d = -64/-4
d = 16
Plug in the value of d in equation (i),
a + 2*16 = 116
a + 32 = 116
a = 116 - 32
a = 84
12th term = 84 + 11* 16 = 84 + 176 = 260